2020
DOI: 10.21203/rs.3.rs-41363/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Climate Change and Trend Analysis of Temperature in Addis Ababa, Ethiopia

Abstract: Background: This paper presents the trend analysis of temperature in Addis Ababa City and the effect of climate change in the study area. The analysis is based on the temperature variation in the capital city of Addis Ababa over two stations - Bole and Entoto. Methods: The Mann-Kendall trend test and Sen’s slope estimate were employed to find the nature of the temperature trend and significance level in Addis Ababa city. Results: It was found that the Mann-Kendall statistic (Z) value for minimum, maximum and a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…This study revealed that as the age of children increased, risk of malaria infection increased by three folds. This finding is in line with a study done in Malawi (31) and a study conducted in Uganda to assess the risk factors associated with malaria infection among under-five children (19), a study done in Zambia [45] and a study done in Awassa District, Ethiopia (32). This could be justified by this is the immediate time (4–5 years of age), in which children participate to look after the cattle.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that as the age of children increased, risk of malaria infection increased by three folds. This finding is in line with a study done in Malawi (31) and a study conducted in Uganda to assess the risk factors associated with malaria infection among under-five children (19), a study done in Zambia [45] and a study done in Awassa District, Ethiopia (32). This could be justified by this is the immediate time (4–5 years of age), in which children participate to look after the cattle.…”
Section: Discussionsupporting
confidence: 90%
“…The difficulty of the processing system might also be another reason for the reduction of enset production in the area. This result was similar to the study by Alemu and Sanford [ 39 ] that was done in the North Omo Zone, Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
“…A few goat populations, such as the Nigerian Dwarf goat, a variant of the West African Dwarf, are well-known for their prolificacy. Goats are also important sources of milk and meat and provide financial stability to pastoral communities and smallholder farmers in arid, semi-arid, and mountainous areas of Africa [9–13].…”
Section: Introductionmentioning
confidence: 99%